Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Transformasional terhadap Kinerja Pegawai Dinas Bina Marga Cipta Karya dan Tata Ruang Prov Sumatera Barat dengan Motivasi Kerja sebagai Variabel Intervening - Sahdatul Jumaiyang; Dori Mittra Candana; Selvi Zola Fenia (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This research aims to test how much influence Organizational Culture and Transformational Leadership Style have on the Performance of Employees of the Highways and Construction and Spatial Planning Department of West Sumatra Province with Work Motivation as an Intervening Variable. The sample in this study amounted to 53 respondents. The population in this study were 53 employees who worked in the West Sumatra Provincial Development and Development Agency for Works and Spatial Planning in 2021/2023. The results of this research are (1) There is a positive and significant influence between organizational culture on work motivation at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province (2) There is a positive and insignificant influence between Transformational Leadership Style on Work Motivation at the Department of Highways Cipta Karya and Spatial Planning of West Sumatra Province (3) There is a positive and insignificant influence between Organizational Culture on Employee Performance at the Department of Highways Cipta Karya and Spatial Planning of West Sumatra Province. (4) There is a positive and insignificant influence between Transformational Leadership Style on Employee Performance at the Cipta Karya Highways Service and West Sumatra Province Spatial Planning. (5) There is a positive and significant influence between Work Motivation on Employee Performance at the Cipta Karya Highways Service and West Sumatra Province Spatial Planning Service. (6) There is a positive and significant influence between Employee Performance on Employee Performance through Work Motivation at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province. (7) There is a positive and insignificant influence between Leadership Style Transformational on Employee Performance through Work Motivation at the Department of Highways, Cipta Karya and Spatial Planning of West Sumatra Province.